Evaluation of portable colposcopy and human papillomavirus testing for screening of cervical cancer in rural China. Issue 1 (7th January 2019) - Newman, Haley; Hu, Jilin; Li, Xiao; He, Jing; Bradford, Leslie; Shan, Songmei; Wu, Xiaomei; Zhu, Bin; Yang, Wenyang; Fu, Bingqin; Zhu, Baosheng; Gao, Guangping
Abstract : Objective: To evaluate the use of a portable, rechargeable colposcope combined with human papillomavirus (HPV) testing, as compared with HPV testing alone, for screening of cervical cancer and pre-cancerous lesions. Methods: This was a cross-sectional study among 488 women in Baoshan County, Yunnan. The women underwent HPV testing followed by Gynocular portable colposcopy with visual inspection with acetic acid. Obvious lesions were biopsied. If portable colposcopy testing was negative but HPV testing was positive, the women underwent follow-up testing with thin-prep cytology and traditional colposcopy. Cervical biopsies were performed for any abnormalities. Histopathology was followed up with diagnosis and treatment. Results: Among 488 women screened with portable colposcopy, 24 women underwent biopsy based on positive colposcopy screening. Of these 24 women, three were HPV positive and 21 were HPV negative. Five women had cervical intra-epithelial neoplasia (CIN) I and one had advanced cervical cancer. Forty-six women tested positive for HPV. Three of these women had screened positive on preliminary colposcopy, with one positive for CIN III/squamous cell carcinoma and one woman with CIN I. Forty-three women underwent follow-up testing with thin-prep cytology. Two women had atypical squamous cells of undetermined significance and five had low-grade squamous intra-epithelial lesions and were biopsied; three women had CIN I, one had CIN II and one had CIN III. HPV testing and portable colposcopy was more sensitive but slightly less specific than portable colposcopy or HPV testing alone. Conclusion: While HPV testing has high sensitivity and specificity for the detection of pre-cancerous and cancerous lesions and portable colposcopy has lower specificity, both methods of detection have low positive predictive value and high negative predictive value. In tandem, HPV testing and portable colposcopy had higher sensitivity for detection among women who underwent biopsies. In clinical practice, portable colposcopy was an effective, easy and affordable tool to transport to villages where cytology is not currently feasible.